THE EMPLOYEE PERFORMANCE ASSESSMENT AND EMPLOYEE TRAINING, ON EMPLOYEE INTENSION - Jeffrey, Ignatius; Prasetya, Agus Budi (Jurnal Aplikasi Manajemen, 2019)
This study aims to examine and analyze the effect of employee performance appraisal and employee learning, to an employee out intentions with employee retention as a mediating variable. High employee turnover rates can result in negative impacts on the company such as decreasing service, decreasing productivity and resulting in increased human resource costs in terms of the cost of training that has been invested and for recruitment and retraining. The XYZ Secondary Data of 2016-2017 shows the turnover of employees. One of the challenges faced by the company is the employee turnover, from the data obtained by employee turnover recorded up to August 2017 of 3.66%, 0.48% above the target year 2017sesar 3.18. This study uses 36 parameters, multiplied by 5 then the required number of samples is 180 respondents. A sample used in this research is 180 employees at some position/position of PT XYZ. A technique of collecting data using observation, interview and questioner and data analysis technique used is the Structural Equation Model (SEM) version 22.0. In further research, researchers can conduct research on aspects other than those studied in this research and are expected to be able to explore other variables such as organizational culture, compensation and benefits, leadership, coaching and mentoring, career development and other variables suspected of having an influence on employee performance in an organization or company.